Design of a 2×2 tapered dielectric‐loaded helical antenna array for INMARSAT‐M satellite system. Issue 11 (26th August 2013) - Manoochehri, Omid; Abbasiniazare, Seyyedpayam; Forooraghi, Keyvan
ABSTRACT In this paper, design and fabrication of an L‐band axial mode 2 × 2 tapered dielectric‐ loaded helical antenna array for international maritime satellite organization (INMARSAT)‐M mobile vehicles are presented. This array has compact size and light weight. By adding a tapered cylindrical dielectric resonator, for satellite communications, important parameters such as gain, side lobe level, impedance matching and axial ratio bandwidth have been improved simultaneously. This array has a gain of 15.1 dB, a radiation pattern with a side lobe level of –21 and a –3 dB axial ratio bandwidth is nearly 15%. These characteristics are suitable for INMARSAT‐M antennas. A good agreement between the simulated and measured results has been achieved. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2600–2604, 2013